2019
DOI: 10.1177/0003489419846138
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Dynamic Voice CT Scan for Complex Airway Patients Undergoing Voice Surgery

Abstract: Introduction: Dynamic voice computerized tomography (DVCT) is a novel technique that provides additional information to characterize laryngeal function for patients with complex airway history that may alter surgical decisions. The goal of this study was to evaluate the impact of DVCT on decision making for reconstructive voice surgery for a cohort of post-airway reconstruction dysphonia patients. Methods: Retrospective chart review at a pediatric tertiary care center for patients with history of complex airwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The majority of imaging studies of the vocal cords has been done using CT 15,16,25 . The most important downside of CT compared to MRI is exposure to, albeit low, ionizing‐ radiation 16 . Comparison studies between dynamic CT and MRI have never been reported, but our MRI study shows excellent identification of the anatomical structures, and thereby closure defects of the vocal cords, comparable to previous CT studies.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The majority of imaging studies of the vocal cords has been done using CT 15,16,25 . The most important downside of CT compared to MRI is exposure to, albeit low, ionizing‐ radiation 16 . Comparison studies between dynamic CT and MRI have never been reported, but our MRI study shows excellent identification of the anatomical structures, and thereby closure defects of the vocal cords, comparable to previous CT studies.…”
Section: Discussionsupporting
confidence: 61%
“…An important benefit of imaging methods such as CT and MRI is the ability to visualize the vocal cords in a three‐dimensional plane, therefore less influenced by the strongly altered anatomy such as severe supraglottic collapse 15,16,25 . Supraglottic constriction during phonation is a common compensatory mechanism in patients with dysphonia, but can also be a sign of architectural distortion after LTS repair 10,26,27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with shortness of breath and history of tracheostomy should increase the awareness of the possibly of an A‐frame deformity. As with other sites of airway obstructions, carefully planning is required 11–20 …”
Section: Discussionmentioning
confidence: 99%